Environmental Geotechnology Proceedings of EGRWSE 2018 - Agnihotri, Arvind Kumar; Reddy, Krishna R.; Bansal, Ajay (Lecture Notes in Civil Engineering,, 2019)
This volume contains selected papers presented during the International Conference on Environmental Geotechnology, Recycled Waste Material and Sustainable Engineering (EGRWSE-2018). The multidisciplinary articles included in this volume cover the fields of environmental management, site characterization, environmental risk assessment, waste disposal, soil and groundwater remediation, habitat protection, and environmental rehabilitation. This volume will be of interest to professionals and researchers working in diverse fields ranging from geotechnical engineering, environmental engineering, hydrogeology, earth science, geochemistry, water engineering, and ecology, among others.